TINJAUAN PEMENUHAN DOKUMEN PENGADAAN BARANG ATAU JASA DAN PERTANGGUNGJAWABAN PERJALANAN DINAS - Natasya Fitria Nadine, (2023)
Procurement of goods or services and official travel are expenditures for goods using the State Revenue and Expenditure Budget. Procurement of goods or services has a major role, namely contract negotiation with the intention of both parties agreeing, therefore the procurement of goods or services has documents on a list of contracts by the provisions containing agreements for the purchase of these goods or services. Likewise, business trips in increasing effectiveness and efficiency in paying official travel expenses to support the implementation of responsibilities and duties. Thus official travel also requires supporting documents that must be fulfilled as a form of accountability. The purpose of compiling this final project report is to find out the procedures for fulfilling documents for the procurement of goods or services and accountability for official travel. In this writing, the data and information collected during the data collection stage were processed using descriptive qualitative analysis techniques.